27-Hydroxycholesterol Alters Synaptic Structural and Functional Plasticity in Hippocampal Neuronal Cultures. Issue 3 (11th February 2019) - Wang, Yushan; An, Yu; Zhang, Dandi; Yu, Huiyan; Zhang, Xiaona; Wang, Ying; Tao, Lingwei; Xiao, Rong
Abstract: This study aimed to explore the neurotoxic effects of 27-hydroxycholesterol (27-OHC), a major circulating cholesterol active derivative in brain on synaptic structural and functional plasticity in primary hippocampal neurons. Newborn SD rat primary hippocampal neurons were treated with 0, 1, 3, 10, and 30 μM 27-OHC for 24 hours. MTT and CCK-8 assays were used to monitor the cell viability of neurons with different treatments. Neurite morphology was assessed by staining for microtubule-associated protein-2 (MAP2) and analyzed by immunofluorescence. Synaptic ultrastructure was evaluated by transmission electron microscopy. Real-time polymerase chain reaction and Western blot analyses were used to evaluate the expression of key synaptic proteins: synaptophysin (SYP), postsynaptic density protein-95 (PSD-95), synaptosomal-associated protein 25 (SNAP-25), growth-associated protein-43 (GAP-43), MAP2, and activity-regulated cytoskeleton-associated protein (Arc). Treatment with 27-OHC at various doses stimulated cell death and resulted in significant decreases in neurite number and length, alteration of synaptic ultrastructure, and downregulated expression of synaptic proteins in a dose-dependent manner. These results suggest that 27-OHC is deleterious for synaptic structural and functional plasticity, which may partially account for its neurotoxic effects.